Severe odontogenic infection in a systemically compromised patient (Research, Society and Development, 2021)
Odontogenic infection is a common health condition in the dental clinic and can represent, in certain situations, a serious health condition with the potential to spread through the fascial spaces of the head, neck and chest region, which require immediate interventions and treatments for not compromise the patient's life. Some pre-existing systemic conditions, such as uncontrolled diabetes mellitus, obesity, alcoholism, and immunosuppression, can accentuate these infections. In this case report, we present a 24-year-old female patient with a severe odontogenic infection, disseminated in the left hemiface, presenting diabetes mellitus and untreated hypertension, being treated in a hospital environment. Patient presented exacerbated pain, dysphagia and trismus. The intraoral examination revealed unsatisfactory oral hygiene, marked mouth opening limitation, absence of element 28, tooth 38 with pericoronitis and signs of nibbling on the left cheek mucosa due to edema. The laboratory tests showed significant changes. Intravenous antibiotic therapy instituted by the medical team of Meropenem 3 times a day and Vancomycin twice a day was started. The treatment chosen was extraction of the infectious focus, drainage of purulent exudate via the alveolar area, abundant irrigation and aspiration of 0.9% saline solution. After improvement in the clinical and laboratory status and control of the patient's glycemic status, she was discharged from the hospital with periodic outpatient control. In the outpatient clinic, the patient improved in her condition, with the volumetric increase regressing and with a slight hardening of the face. Follows the systemic care in an outpatient clinic by the medical team. Thus, infection in patients with systemic involvement requires an immediate and multidisciplinary approach to ensure a good prognosis